High-resolution mtDNA evidence for the late-glacial resettlement of Europe from an Iberian refugium - Pereira, Luísa; Richards, Martin; Goios, Ana; Alonso, Antonio; Albarrán, Cristina; Garcia, Oscar; Behar, Doron M.; Gölge, Mukaddes; Hatina, Jiři; Al-Gazali, Lihadh; Bradley, Daniel G.; Macaulay, Vincent; et al.

(untitled) (Genome Research, 2005)
The advent of complete mitochondrial DNA (mtDNA) sequence data has ushered in a new phase of human evolutionary studies. Even quite limited volumes of complete mtDNA sequence data can now be used to identify the critical polymorphisms that define sub-clades within an mtDNA haplogroup, providing a springboard for large-scale high-resolution screening of human mtDNAs. This strategy has in the past been applied to mtDNA haplogroup V, which represents <5% of European mtDNAs. Here we adopted a similar approach to haplogroup H, by far the most common European haplogroup, which at lower resolution displayed a rather uninformative frequency distribution within Europe. Using polymorphism information derived from the growing complete mtDNA sequence database, we sequenced 1580 base pairs of targeted coding-region segments of the mtDNA genome in 649 individuals harboring mtDNA haplogroup H from populations throughout Europe, the Caucasus, and the Near East. The enhanced genealogical resolution clearly shows that sub-clades of haplogroup H have highly distinctive geographical distributions. The patterns of frequency and diversity suggest that haplogroup H entered Europe from the Near East ∼20,000–25,000 years ago, around the time of the Last Glacial Maximum (LGM), and some sub-clades re-expanded from an Iberian refugium when the glaciers retreated ∼15,000 years ago. This shows that a large fraction of the maternal ancestry of modern Europeans traces back to the expansion of hunter-gatherer populations at the end of the last Ice Age.